Study of Application Liquid Organic Fertilizer and Monosodium Glutamate on Chlorophyll and Yield of Cannabis - Agus Suprapto; Esna Dilli Novianto; Mahdalina Mursilati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Cannabis (Canna edulis Kerr.) is a plant source of local food that contains carbohydrates so that cannabis is included as an alternative food crop to replace rice. The purpose of this study was to obtain a dose of liquid organic fertilizer (POC) and monosodium glutamate (MSG) on the chlorophyll content and yield of cannabis. The research was conducted from October 2020 to April 2021 on agricultural land in Plumbon Village, Selopampang, Temanggung with an altitude of 460 m above sea level. The research method was arranged in a completely randomized block design using a factorial experiment consisting of two factors and repeated three times. The first factor is the POC dose with levels: 0 mL/L, 2 mL/L, 3 mL/L, and 4 mL/L. The second factor was the dose of MSG consisting of: 0 g/plant, 3 g/plant, 6 g/plant, and 9 g/plant. Data were analyzed using analysis of variance with 1% and 5%. Data that showed significant differences were tested for orthogonal polynomial. The results showed that the addition of 2-3 mL/L of POC gave very significant differences in the amount of leaf chlorophyll and the fresh weight of tubers. The addition of MSG gave significantly different results to the fresh weight of tubers. The dose interaction of POC and MSG was significantly different to the fresh weight of tubers and significantly different to the amount of leaf chlorophyll.